Developmental Dyscalculia and Automatic Magnitudes Processing: Investigating Interference Effects between Area and Perimeter - Eidlin-Levy, Hili; Rubinsten, Orly (Frontiers in Psychology, 2017)
The relationship between numbers and other magnitudes has been extensively investigated in the scientific literature. Here, the objectives were to examine whether two continuous magnitudes, area and perimeter, are automatically processed and whether adults with developmental dyscalculia (DD) are deficient in their ability to automatically process one or both of these magnitudes. Fifty-seven students (30 with DD and 27 with typical development) performed a novel Stroop like task, requiring estimation of one aspect (area or perimeter) while ignoring the other. In order to track possible changes in automaticity due to practice, we measured performance after initial and continuous exposure to stimuli. Similar to previous findings, current results show a significant group X congruency interaction, evident beyond exposure level or magnitude type. That is, the DD group systematically showed larger Stroop effects. However, analysis of each exposure period showed that during initial exposure to stimuli, the DD group showed larger Stroop effects in the perimeter and not in the area task. In contrast, during the continuous exposure to stimuli, no triple interaction was evident. It is concluded that both magnitudes are automatically processed. Nevertheless, individuals with DD are deficient in inhibiting irrelevant magnitude information in general and specifically struggle to inhibit salient area information after initial exposure to perimeter comparison task. Accordingly, the findings support the assumption that the phenomenon of DD involves a deficiency in multiple cognitive components, including domain-specific and domain-general cognitive functions.